Pygmy Blue Whale Home Ranges and Their Overlaps with Indonesian and Australian Marine Protected Areas: Comparison between a-LoCoH and BBMM Methods - Sahri Achmad; Jak Charlotte; Murk Albertinka J.; van Lammeren Ron J. (BIO Web of Conferences, 2024)
Information on the distribution of marine migratory species is lacking, and for a long time, these species have been overlooked in the designation of Marine Protected Areas (MPAs). This study analysed the home range of pygmy blue whales (PBWs) from western Australia to eastern Indonesia to be able to assess the overlap with current MPAs. In this study, data from 11 individual PBWs tagged in the Perth Canyon were used. Two home range methods, adaptive Local Convex Hull (a-LoCoH) and Brownian Bridge Movement Model (BBMM), were performed and compared to identify core use areas and connections between these areas (i.e., migration corridors). By assessing the relative properties and visually inspecting the home ranges, 90% BBMM (home range and migration corridor) and 50% BBMM (core use area) are chosen as the best results, because they cover the connected core-use areas to a large extent. The home ranges that were covered by current MPAs were only 2% in Indonesia and 16% in Australia. Important migration corridors without current protection are in the east Savu Sea, south of Timor Island, and wider Banda Sea. It is noteworthy that comparing methods is relevant to be able to choose the most suitable method for the data used and the goal of this study. The limited overlap between the calculated home ranges and the MPAs of the Indonesian waters articulates the importance of in-depth scientific studies to be able to evaluate, implement and develop marine conservation planning.